2005
DOI: 10.1111/j.1875-595x.2005.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride concentration of bottled water, tap water, and fluoridated salt from two communities in Mexico

Abstract: Some water samples had amounts of fluoride exceeding the maximum recommended levels. Salt fluoride levels were within regulation limits. Monitoring of fluoride content of both bottled and tap water is strongly advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…In our study, we did not collect water samples to analyse them for fluoride. Previous studies in this community have indicated that the fluoride content of bottled water varies widely from negligible to above optimal, whereas tap water in this community contains negligible amounts of fluoride 15,31 .…”
Section: Discussionmentioning
confidence: 78%
“…In our study, we did not collect water samples to analyse them for fluoride. Previous studies in this community have indicated that the fluoride content of bottled water varies widely from negligible to above optimal, whereas tap water in this community contains negligible amounts of fluoride 15,31 .…”
Section: Discussionmentioning
confidence: 78%
“…The reported fluoride concentration in drinking water in the two areas was well under the recommended level of <0.7 mg/L (0.24 mg/L in the rural area and 0.15 mg/L in the urban area).…”
Section: Methodsmentioning
confidence: 78%
“…All of the data from Houston, Los Angeles, and New Hampshire, USA, and Mexico and Brazil indicate the difficulty is maintaining consistent levels. One explanation why the levels might fluctuate is due to fluoride reacting with other dissolved chemicals in the water.…”
Section: Discussionmentioning
confidence: 99%
“…A study of two communities in Mexico showed that tap water samples that were analyzed had a significant difference, with some water samples exceeding maximum recommended levels. Martinez‐Mier et al . concluded that monitoring the fluoride content of both bottled and tap water is strongly advised.…”
Section: Introductionmentioning
confidence: 99%